Gas exchange by the mesic-origin, arid land plantation species Robinia pseudoacacia under annual summer reduction in plant hydraulic conductance. (28th March 2018) - Miyazawa, Yoshiyuki; Du, Sheng; Taniguchi, Takeshi; Yamanaka, Norikazu; Kumagai, Tomo'omi
Abstract: The mesic-origin plantation species Robinia pseudoacacia L. has been successfully grown in many arid land plantations around the world but often exhibits dieback and reduced growth due to drought. Therefore, to explore the behavior of this species under changing environmental conditions, we examined the relationship between ecophysiological traits, gas exchange and plant hydraulics over a 3-year period in trees that experienced reduced plant hydraulic conductance ( G p ) in summer. We found that the transpiration rate, stomatal conductance ( G s ) and minimum leaf water potential (Ψlmin ) decreased in early summer in response to a decrease in G p, and that G p did not recover until the expansion of new leaves in spring. However, we did not observe any changes in the leaf area index or other ecophysiological traits at the leaf level in response to this reduction in G p . Furthermore, model simulations based on measured data revealed that the canopy-scale photosynthetic rate ( A c ) was 15–25% higher than the simulated A c when it was assumed that Ψlmin remained constant after spring but almost the same as the simulated A c when it was assumed that G p remained high even after spring. These findings indicate that R. pseudoacacia was frequently exposed to a reduced G p at the study site but offset its effects on A c by plastically lowering Ψlmin to avoid experiencing any further reduction in G p or G s .